Frequency of symptoms, determinants of severe symptoms, validity of and cut-off score for Menopause Rating Scale (MRS) as a screening tool: A cross-sectional survey among midlife Nepalese women - Chuni Neena; Sreeramareddy Chandrashekhar T (BMC, 2011)
Abstract Background Majority of Nepalese women live in remote rural areas, where health services are not easily accessible. We determined the validity of Menopause Rating Scale (MRS) as a screening tool for identification of women with severe menopausal symptoms and cut-off MRS score for referral. Methods A cross-sectional survey was carried out between February and August, 2008. Trained health workers administered MRS and a questionnaire to 729 women (40 to 65 years) attending health screening camps in Kaski district of Western Development Region of Nepal. Information about demographics, menopausal status, and use of hormone replacement therapy (HRT), chronic disease, self-perceived general health and reproductive history was also collected. Menopausal status was classified according to the Staging of Reproductive Ageing Workshop (STRAW). We calculated rates of menopausal symptoms, sensitivity, and specificity and likelihood ratios of MRS scores for referral to a gynaecologist. We also carried out multivariate analyses to identify the predictors for referral to a gynaecologist for severe symptoms. Results A total 729 women were interviewed. Mean age at menopause was 49.9 years (SD 5.6). Most frequently reported symptoms were, sleeping problems (574, 78.7%), physical and mental exhaustion (73.5%), hot flushes (508, 69.7%), joint and muscular discomfort (500, 68.6%) and dryness of vagina (449, 61.6%). Postmenopausal women (247, 33.9%) and perimenopausal (215, 29.5%) women together experienced significantly higher prevalence of all symptoms than the premenopausal (267, 36.6%) women. MRS score of ≥16 had highest ratio for (sensitivity + specificity)/2. Women who reported urogenital symptoms [OR 5.29, 95% CI 2.59, 10.78], and self perceived general health as poor [OR 1.29, 95% CI 1.11, 1.53] were more likely to be referred to a gynaecologist for severe menopausal symptoms. While women reporting somatic [OR 0.72, 95% CI 0.63, 0.82] and psychological [OR 0.86, 95% CI 0.74, 0.99] symptoms were less likely to be referred. Conclusion MRS may be used as a screening tool at a cut-off score of ≥16 with least misclassification rate. However, its utility may be limited by woman's general health status and occurrence of urogenital symptoms.